Caste and Social Inequality in Aravind Adiga's The White Tiger - Dr Sarita Goyal (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Aravind Adiga's The White Tiger offers a compelling critique of the entrenched caste system and pervasive social inequality in contemporary India. Through the eyes of the protagonist, Balram Halwai, the novel examines the oppressive structures that sustain economic and social divisions. Balram’s journey from a village in the "Darkness" to becoming an entrepreneur in the urban "Light" of Bangalore serves as a microcosm of the larger societal shifts and tensions. Adiga employs vivid symbolism, such as the Rooster Coop metaphor, to highlight the inescapable nature of caste confinement and the desperation for escape. The novel's narrative style and use of dark humor underscore the systemic corruption and moral ambiguities that complicate the pursuit of social mobility. This research paper delves into the representation of caste and social inequality in The White Tiger, analyzing key characters, symbols, and themes to understand how Adiga portrays the stark contrasts between the rich and the poor, and the challenges of achieving genuine social mobility in an inherently unjust society.